2012
DOI: 10.5603/fhc.2012.0030
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment plasma levels and diagnostic utility of hematopoietic cytokines in cervical cancer or cervical intraepithelial neoplasia patients

Abstract: Abstract:In this study, we compared plasma levels and the diagnostic utility of hematopoietic growth factors (HGFs) with SCC-Ag in cervical cancer patients in relation to control groups and cervical intraepithelial neoplasia (CIN) patients and healthy subjects. Pretreatment plasma levels of HGFs (SCF, GM-CSF, G-CSF and M-CSF) were determined by the use of immunoenzyme assay (ELISA), and SCC-Ag by chemiluminescent microparticle immunoassay (CMIA). Significantly different concentrations of GM-CSF, G-CSF and M-CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
4
12
1
Order By: Relevance
“…Only the plasma levels of TIMP-2 were statistically significantly lower when compared to healthy controls. These findings are in agreement with our previous study showing that the median levels of M-CSF in cervical cancer patients are higher (510.55 pg/mL) than in healthy subjects (290.82 pg/mL) [32]. Our observation is supported by data regarding M-CSF from a previous report by Ławicki et al [33] in breast cancer patients.…”
Section: Discussionsupporting
confidence: 94%
“…Only the plasma levels of TIMP-2 were statistically significantly lower when compared to healthy controls. These findings are in agreement with our previous study showing that the median levels of M-CSF in cervical cancer patients are higher (510.55 pg/mL) than in healthy subjects (290.82 pg/mL) [32]. Our observation is supported by data regarding M-CSF from a previous report by Ławicki et al [33] in breast cancer patients.…”
Section: Discussionsupporting
confidence: 94%
“…Results of this study suggest that combining VEGF with CA125 and HE4 measurements might enable improved early detection of this cancer as compared with use of either marker alone or of both comparative tumor markers. This observation is in accordance to our previous papers, in which we evaluated diagnostic criteria of selected cytokines and commonly used tumor markers in various gynecological malignancies [51,57,58]. Several studies have found sensitivity to be greater than in either marker alone: VEGF and CEA (carcinoembrionic antigen) in colorectal [59] or HE4 and CA125 in ovarian cancer patients [5,45].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have confirmed this observation - they found sensitivity to be greater than in either marker used alone: MMP-7, CCL18 (CC chemokine 18), CCL11 (CC chemokine 11) and CA125 in ovarian cancer (SE in the early stages 94.4%) [46]. This conclusion is also in accordance with our previous papers in which the diagnostic criteria of selected cytokines and aforementioned tumor markers were evaluated in various gynecological malignancies [47, 48]. Diagnostic specificity (SP) reached very high and equal values for all biomarkers studied and this was in accordance [40, 43] with the available literature in the course of various malignant and benign diseases.…”
Section: Discussionsupporting
confidence: 85%